A longitudinal qualitative study of the UK general practice workforce experience of COVID-19. (4th August 2022) - Burn, Emily; Fisher, Rebecca; Locock, Louise; Smith, Judith
Abstract: Background: The COronaVIrus Disease 2019 (COVID-19) pandemic has led to significant re-organisation of general practice in the United Kingdom and around the world. The general practice workforce has led changes to their services, often dealing with high levels of uncertainty. The way in which many practitioners consult has shifted significantly, and there has been an increase in the number of phone and online consultations. We know very little about how those working in general practice experienced the service reorganisation introduced in the first year of the COVID-19 pandemic. Aim: The aim of this project was to describe the changes in the delivery of general practice in the United Kingdom in the first year of the COVID-19 pandemic. Furthermore, to explore primary care practitioners' and managers' experiences of change within general practice during this time and investigate shifts in perceptions of professional identities. Method: We conducted a longitudinal qualitative study that captured narrative accounts from 17 primary care practitioners and managers across England and Scotland. Each participant submitted narrative accounts in the first year of the COVID-19 pandemic using self-recorded or written contributions, or via an interview if preferred. These were analysed using a grounded theory approach, with thematic coding used to construct common themes. Findings: Participants' narratives describe the challenges COVID-19 presented to general practice. Responses mirror the shifts in the pandemic and its management – from an initial sense of autonomy but uncertainty, to a period of stability and patients' increasing frustration. The re-organisation of general practice has affected practitioners' views of their work and their role as clinicians. Participants' narratives were framed profoundly by the importance of their relationships with patients. This analysis of practitioners' and managers' narratives highlights the need for further exploration of how to support the general practice workforce's well-being longer term in a context of increased demand and significant change.